Metody matematyczne w dydaktyce ubezpieczeń na studiach ekonomicznych - Kowalczyk, Patrycja; Ronka-Chmielowiec, Wanda (Mathematical methods in the didactics of insurance on economic studies, 2010)
In universities economics the issues associated with functioning of insurance institutions are a part of the curricula in courses of finance and accounting. The authors present curricula of lectures which contain applying mathematics in insurance. The authors discuss issues in the curriculum of financial mathematics and insurance for the courses of the computer science and econometrics and computer science in the business. The authors also present models of the capitalization of money and other models which can be used in life insurance and superannuation plan
Didactics of Mathematics, 2010, Nr 7 (11), s. 59-66
Keywords: actuarial methods; financial and insurance mathematics; insurance; risk management